Análise genética molecular (RAPD) de Conopophaga melanops, Vieillot 1818 (Aves, Conopophagidae), em escala fina da Mata Atlântica e sua implicação para a conservação da espécie - Lunardi, Vitor de Oliveira (2004)
Conopophaga melanops is an endemic Atlantic forest bird species that had its habitat drastically fragmented by the historical process of massive deforestation. Today, its populations have survived isolated in small fragments and a few continuous forests, compromising the potential of the species to overcome natural and anthropic disturbances. The aim of this study was to estimate genetic differentiation among and within three populations of C. melanops in the major protected continuum of an Atlantic forest reminiscent using RAPD-PCR, to provide a better understanding of the geographical patterns of genetic variation of the species in fine scale and original context. The genetic molecular analyses showed a statistically significant genetic divergence among the three C. melanops populations in a continuum transect of 250 km. Primarily, this could be explained by the assumed sedentarism of the species and by the geographical barriers to gene flow. Pleistocene refuges and recent human impact could be adictional factors to explain the current genetic diferentiation.